Sheep immune response against a novel recombinant enterotoxemia and infectious necrotic hepatitis vaccine in Türkiye - Ekinoglu, Dilek Nur; Celik, Venhar; Gul, Esra; Kalender, Hakan; Ongor, Hasan; Cetinkaya, Burhan (Bmc, 2025)
BackgroundClostridial diseases are common in ruminants all over the world. This study investigated the efficacy of a novel recombinant vaccine developed against enterotoxemia and infectious necrotic hepatitis in sheep.ResultsPlasmids carrying the Clostridium novyi type B alpha toxin gene (CnBtcn-alpha), Clostridium perfringens type C beta toxin gene (CpCcpb) and C. perfringens type D epsilon toxin gene (CpDetx) were constructed and the plasmids were transferred to Escherichia coli. Unpurified protein obtained from E. coli cell lysate supernatant was used to prepare the recombinant vaccine. The vaccine was prepared in three different formulas (RV100, RV200 and RV400), with 100, 200 and 400 mu g of each protein in one vaccine dose. RV400 was preferred to immunise sheep as the antitoxin titres in the pooled blood serum of rabbits administered with this vaccine were determined to be above the minimum values specified in European Pharmacopoeia (10 IU/mL for beta, 5 IU/mL for epsilon, and 3.5 IU/mL for alpha). A total of 24 Akkaraman breed sheep with no antibodies against the relevant toxins were used for the experiment. All the animals in three groups (recombinant vaccine group, commercial polyvalent vaccine group and negative control group), each consisting of eight sheep, were vaccinated twice with an interval of 21 days and, the antitoxin titres were measured 14 days after the second vaccination by the mouse toxin neutralization test. The average antitoxin titres in sheep immunised with RV400 were calculated as 9.75 +/- 1.28 IU/mL for C. perfringens beta, 13.75 +/- 1.98 IU/mL for C. perfringens epsilon and 5.50 +/- 0.93 IU/mL for C. novyi alpha toxins. On the other hand, the average values in sheep immunised with commercial vaccine were detected as 8.00 +/- 2.14 IU/mL, 4.25 +/- 1.67 IU/m L and 6.50 +/- 0.93 IU/mL for C. perfringens beta, C. perfringens epsilon and C. novyi alpha, respectively. No antitoxin titre was detected in sheep in the negative control group (PBS). A statistically significant difference was observed between the recombinant and commercial vaccine groups in terms of C. perfringens epsilon antitoxin titres (P = 0.0002).ConclusionsThe present study was the first to investigate the efficacy of a combined recombinant vaccine prepared from unpurified proteins against enterotoxemia and infectious necrotic hepatitis and, the results suggested that it shows promise for protecting sheep against these diseases.
Keywords: Enterotoxemia; Infectious necrotic hepatitis; Immune response; Recombinant vaccine; Sheep